Isolation and identification of a high-efficiency oil-degrading Klebsiella pneumoniae strain from kitchen waste and evaluation of its degradation performance - Ding, Wenqiao; Xu, Chongli; Zhang, Mengyi; Xie, Ying; Li, Fei; Huang, Qiuting (Frontiers in Microbiology, 2026)
In view of the excessive grease content in kitchen wastewater and the limited oil removal efficiency of conventional treatment systems, this study isolated a highly efficient oil-degrading bacterium (strain Y1) from soil beneath a kitchen waste pipeline and investigated its degradation performance. Through morphological observation, biochemical tests, and 16S rRNA gene sequencing, strain Y1 was identified as Klebsiella pneumoniae. The growth characteristics and oil degradation performance revealed the optimal degradation conditions to be 35 °C, pH 7.0, and 180 r/min. Under these conditions, the oil degradation rate reached 48.7%. In a simulated treatment of actual kitchen oil-rich wastewater, strain Y1 achieved the chemical oxygen demand (COD) removal rate of 62% in 48 h (reaching 62.8% at 66 h) and an oil degradation rate of 60.7% in 96 h (slightly increasing to 60.9% at 108 h). These results highlight the potential of strain Y1 for practical application in the bioremediation of oily wastewater. This study provides a new microbial resource and technical reference for the biological treatment of kitchen grease wastewater.